(untitled) (Islas, 2024)
Introduction: For the elaboration of this article, random fragments of Martí’s chronicles Escenas Norteamericanas and Carpenter’s Revista Carteles were selected, since they allowed to determine the rhetorical strategies and idiomatic signs that build their multicultural ethos. Methods: This research is conducted using discourse analysis from a rhetorical perspective, which becomes descriptive and involves message interpretation, supported by a qualitative methodology. Results: The discovery of the multicultural ethos emerging from the analyzed chronicles offers a contemporary and comprehensive view of the situation of immigrants in today’s societies, which present diverse cultures. Conclusions: In Martí and Carpentier, a cultured pre-discursive ethos converges, validating the multicultural ethos presented in the analyzed chronicles, where the displayed ethos and the spoken ethos intertwine to uphold the sincerity of their words.